PEMBERDAYAAN PENDIDIKAN AGAMA ISLAM ERA INDUSTRIALISASI-GLOBALISASI DI MADURA - M. Muhlis Sholichin, M. Muhlis Sholichin (STAIN PAMEKASAN, 2012)
Abstrac Islamic education can be concluded as an individual and institutional attempts which are done to shape Muslim personality that enable to perform Islamic teaching. In facing the era of industrialization and globalizationn, Islamic education faces several challenges and problems that are caused by the changes of global-industry sociaety. The changes demand the role of Islamc education. It must be more powerful to protect the students from the anomaly of Muslim thought and life patterns. . Kata-kata kunci Islamic education, industrialization-globalization, change.